Strategi Pengurangan Defect Berbasis Six Sigma Pada Make To Order Customize Multi Product (Produk Kemasan Pada CV. Berkah Kemasan) - Fadlan, Fui; Cahyo, Winda Nur (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
In this study, the Six Sigma technique is used with the DMAIC (Define, Measure, Analyze, Improve, and Control) level in studying the problems that occur. Based on studies conducted on three types of manufacturing defects, namely the Rise Color method, Pond method and joint glue, each failure in the shade method has 53% or 6897 packaging defects, in the pond method 28% or 3623 applications and in the glue method. 20% or 2593 packages with a total packaging defect of 13113. Based on the calculation, the DPMO price is 7.262 with a sigma of 3.95, for the final result of UCL 0.024902 and LCL 0.019327. Mainly based entirely on the identity of the use of the most dominant fishbone diagram in humans and the techniques used for development are carried out using the 5W + 1H technique